Connecting the "Others": White Anti-Semitic and Anti-Muslim Views in America. Issue 1 (2nd January 2023) - Gerteis, Joseph; Rotem, Nir
ABSTRACT: Drawing from recent work on "otherness" and social boundaries in America, we investigate anti-Muslim and anti-Jewish opinion among white Americans. After outlining the logic of the comparison, we use nationally representative data to analyze these forms of othering. Although anti-Muslim opinion is more extensive, the two track together empirically and share a cultural logic as connected forms of ethno-religious boundary-making. Latent class analysis shows that anti-Semitism is nested within anti-Muslim attitudes, with political and religious identifications as consistent predictors of opinion. We conclude with a reflection on politicized boundary-making and the relationship between extreme and mainstream views of the "other."